Economic Viability of Tomato Cultivation in Organic Farming System - José dos Santos Neto; Kátia Regina Freitas Schwan-Estrada; José Ozinaldo Alves de Sena; Tiago Santos Telles (Brazilian Archives of Biology and Technology, 2017)
ABSTRACT The aim of the present study is to evaluate the economic viability of tomato cultivation in a system of organic farming, and to compare it with the conventional farming system. The fixed and variable costs of both cultivation systems were calculated, as well as the costs of disease control with the application of alternative products and pesticides. The revenues were computed using commercial production and the direct sales price. The total cost per area was higher in the conventional system, while the cost per plant was greater in the organic system, since it used a lower plant population density. In the conventional system, 2.33 times more was spent on plant management, due to the fact that the number of sprayings was greater than that carried out in organic farming. We further find that companion planting with other species such as coriander, in addition to helping with the management of the main crop, is important for economic sustainability as it is an extra source of income. Considering the specificities of the two systems, the profitability of organic cultivation, even accounting for its lower productivity , could exceed that of conventional cultivation.